Upaya Peningkatan Hasil Belajar PAI Siswa Melalui Metode Diskusi Di Kelas X SMA Negeri 1 Kec. Mungka Tahun 2024-2025 - Bela, Okta (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aimed to improve students' learning outcomes in Islamic Education through the implementation of group discussion methods. The classroom action research was conducted on 10th-grade students at [Nama Sekolah] High School. The results showed that the group discussion method was effective in improving students' understanding of the material, especially on the topic of avoiding free sex and zina. There was a significant increase in students' average scores after the implementation of the group discussion method. In addition, students also showed improvements in terms of activeness, critical thinking skills, and cooperation. The implications of this study are that the group discussion method can be an effective alternative in teaching Islamic Education